PENGARUH BRAND IMAGE GOJEK TERHADAP LOYALITAS KONSUMEN (STUDI KASUS EFEK COVID-19 KONSUMEN KARAWACI TEGAL BARU TANGERANG) - Andres Dharma Nurhalim (Jurnal Bina Manajemen, 2020)
COVID-19 caused many significant impacts on various businesses in Indonesia. This outbreak was first announced by the government in early March in 2020 and as a result online transportation companies also have the impact of a decrease in services due to the outbreak. This study aims to determine the effect of brand image gojek on consumer loyalty when the covid 19 effect takes place. The analytical method used by the author in conducting this research is to use quantitative research with a population of 150 respondents which is a community that lives in Karawaci, Tangerang. In carrying out the data collection is done by distributing questionnaires in which there are several items of statement. in this study the variables are divided into several parts including Brand Image (X) and Consumer Loyalty (Y) as the dependent variable. To measure the magnitude of the effect on these variables, the authors use the linear regression analysis method. From the results of the analysis it was found that there is a significant and simultaneous influence on the brand image of the object of consumer loyalty